Chronic Treatment With Qiliqiangxin Ameliorates Aortic Endothelial Cell Dysfunction in Diabetic Rats. (March 2015) - Chen, Fei; Wu, Jia-Le; Fu, Guo-Sheng; Mou, Yun; Hu, Shen-Jiang
Qiliqiangxin (QL), a traditional Chinese medicine, has been shown to be beneficial for chronic heart failure. However, whether QL can also improve endothelial cell function in diabetic rats remains unknown. Here, we investigated the effect of QL treatment on endothelial dysfunction by comparing the effect of QL to that of benazepril (Ben) in diabetic Sprague-Dawley rats for 8 weeks. Cardiac function was evaluated by echocardiography and catheterization. Assays for acetylcholine-induced, endothelium-dependent relaxation (EDR), sodium nitroprusside-induced endothelium-independent relaxation, serum nitric oxide (NO), and nitric oxide synthase (NOS) as well as histological analyses were performed to assess endothelial function. Diabetic rats showed significantly inhibited cardiac function and EDR, decreased expression of serum NO and phosphorylation at Ser 1177 on endothelial NOS (eNOS), and impaired endothelial integrity after 8 weeks. Chronic treatment for 8 weeks with either QL or Ben prevented the inhibition of cardiac function and EDR and the decrease in serum NO and eNOS phosphorylation caused by diabetes. Moreover, either QL or Ben suppressed inducible NOS (iNOS) protein levels as well as endothelial necrosis compared with the diabetic rats. Additionally, QL prevented the increase in angiotensin-converting enzyme 1 and angiotensin II receptor type 1 in diabetes. Thus, chronic administration of QL improved serum NO production, EDR, and endothelial integrity in diabetic rat aortas, possibly through balancing eNOS and iNOS activity and decreasing renin–angiotensin system expression.